Tingkat Kesadahan Total Air Bersih Di Desa Cikedokan (Implementasi Program Pengabdian Kepada Masyarakat PT Medialab Indonesia dan Universitas Pelita Bangsa) - Rizal Al Afghani; Putri Anggun Sari (Prosiding Sains dan Teknologi, 2022)
The clean water used by the residents of Cikedokan Village is used for sanitation hygiene purposes. The clean water supply facility is in the form of a drilled well and information regarding the quality of the water produced and the content of dissolved solids in it is unknown. Therefore it is necessary to test the quality of borehole water, one of which is the chemical parameter in the form of hardness or hardness level. The hardness determination method used in this study uses Inductively Coupled Plasma to determine Ca2+ and Mg2+ content, sampling locations were carried out at 15 coordinate points with a yield of 73.33% of all sampling points indicating that clean water in Cikedokan Village is included in the medium criteria with hardness interval 50-150 mg/L; 20% falls into the soft criteria and 1 sampling point indicates that the clean water in that place is included in the hard category with a value of 162 mg/L. Laboratory test results for the sulfate parameter were 51.3 mg/L. From the results of the analysis that has been carried out, it can be concluded that the majority (93%) of the clean water at the 15 sampling point locations has met the quality standards according to the environmental quality standards contained in the Minister of Health Regulation Number 32 of 2017.